'Mediatization': Media Theory's Word of the Decade - John Corner (Media Theory, 2018)
This short commentary looks at aspects of the debate about the term ‘mediatization’, paying particular attention to recent, cross-referring exchanges both in support of the concept and critical of it. In the context of its widespread use, it suggests that continuing questions need to be asked about the conceptual status of the term, the originality of the ideas it suggests and the kinds of empirical project to which it relates.